The Effect of Provision Kur on The Development of UMKM in Padangsidimpuan - Sry Lestari (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
The purpose of the People's Business Credit (KUR) is to assist the community in developing Micro, Small and Medium Enterprises. The background of this research is how the implementation of the People's Business Credit, and whether the program is running effectively according to the plan that has been determined by the government in accordance with its objectives. This study aims to determine the effect of People's Business Credit on the improvement of Micro, Small and Medium Enterprises in Padangsidimpuan. This research is a quantitative research, namely research that uses numbers in the presentation of data and analysis that uses statistical tests. The population of this research is 310 micro and small business actors and the sample taken is 76 people using purposive sampling method. Data collection techniques using a questionnaire. Data analysis techniques and multiple regression. The results of this study indicate the effectiveness of people's business credit (KUR) has a significant influence on micro and small medium enterprises with a tcount t table (7.110 1.666), then H0 is rejected H1 is accepted, it means that there is an effect of people's business credit on micro, small and medium enterprises in Padangsidimpuan.